Estimativa dos custos associados a surtos de salmonelose veiculada por produtos de origem animal para o Sistema Único de Saúde do Brasil - Flavia Borges Mesquita (2017)
The foodborne diseases are a growing public health problem in many countries. Among these diseases, salmonellosis, an infection caused by the bactéria of the genus Salmonella, is one of the most frequent of those transmitted by food of animal origin, causing not only damage to the health of the population but also great financial impact, even in more developed countries. Faced with difficulties in obtaining certain information, quantitative modeling techniques can be used to estimate data that increase knowledge about diseases. The objective of this study was to estimate the costs of outbreaks of salmonellosis associated with the ingestion of animal products by means of a partial budget model with Monte Carlo simulation. The estimated total cost of outbreaks of salmonellosis due to consumption of animal products, reported to the Ministry of Health in the period from 2008 to 2016 was R$ 3,754,920.26. The average number of days of hospitalization was being the variable that shows possesses Greater relation to the final result, followed by the average number of days lost due to hospitalization. The definition of a model for estimating the costs of salmonellosis outbreaks associated with the ingestion of products of animal origin helps to show not only the financial impact of the costs of this disease in our country, but also the better visualization of the magnitude of the problem, With a view to making decisions among the managers involved.